Systematic Review and Critical Analysis on Dietary Supplements for Male Infertility: From a Blend of Ingredients to a Rationale Strategy - Garolla, Andrea; Petre, Gabriel Cosmin; Francini-Pesenti, Francesco; De Toni, Luca; Vitagliano, Amerigo; Di Nisio, Andrea; Grande, Giuseppe; Foresta, Carlo (Frontiers in Endocrinology, 2022)
Content: Dietary supplements (DS) for male infertility marketed in Italy were evaluated for composition, concentration of ingredients and recommended daily dose. A systematic review of literature identified ingredients potentially effective on sperm parameters and their minimal effective daily dose (mED). Objective: critically evaluate the composition and efficacy of DS marketed in Italy. Design, Setting and Participants: Systematic review of randomized controlled trials. Evidence Acquisition: A formula allowed us to classify the expected efficacy of each DS, based on composition. Each DS was scored and included into three classes of expected efficacy: high, low and none. Evidence Synthesis: Among 24 supplements, 3 (12,5%) fall in high, 9 (37,5%) in lower and 12 (50,0%) in no expected efficacy class. DS composition showed 36 substances, 18 with no literature on male fertility and 18 showing positive effect on sperm parameters, thus considered potentially active ingredients (PAI). All DS were mixtures of ingredients, containing from 2 to 17 different substances. Fifteen supplements (65.2 %) contained at least 1 ingredient without evidence of efficacy and 21 formulations had PAI dosed below mED. Some PAI were associated to the improvement of specific sperm parameters. Conclusions: DS were usually blends of many substances, that are frequently employed at negligible dose or without any evidence of efficacy on male reproduction. Some ingredients have been demonstrated to be effective on specific sperm parameters by RCTs. We report a list of ingredients with potential efficacy on specific sperm parameters, aimed to allow a tailored use of DS. Patient summary: The market of DS for male infertility offers products with potential efficacy in the improvement of sperm parameters but also many with uncertain effect. Based on current scientific literature, our study can help in the choice of DS that are more likely to be effective on specific sperm alterations, so providing the best supplementation for each patient.